2D Materials: Rotation‐Misfit‐Free Heteroepitaxial Stacking and Stitching Growth of Hexagonal Transition‐Metal Dichalcogenide Monolayers by Nucleation Kinetics Controls (Adv. Mater. 25/2015). (1st July 2015) - Heo, Hoseok; Sung, Ji Ho; Jin, Gangtae; Ahn, Ji‐Hoon; Kim, Kyungwook; Lee, Myoung‐Jae; Cha, Soonyoung; Choi, Hyunyong; Jo, Moon‐Ho
<x xml:space="preserve">Abstract</x> On page 3803, M.‐H. Jo and co‐workers demonstrate heteroepitaxial growth of MoS2 and WS2 monolayer (ML) semiconductors. Two different growth modes, i.e., vertical stacking and lateral stitching, can be controlled by the nucleation kinetics during sequential monolayer growth. These enable large‐area ML heterostructures to be fabricated without interlayer rotation misfits; thereby, this method can offer possibilities for the realization of controlled 2D semiconductor superstructures on large scales.